1996
DOI: 10.1523/jneurosci.16-20-06414.1996
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory GABA Responses in Embryonic and Neonatal Cortical Slices Demonstrated by Gramicidin Perforated-Patch Recordings and Calcium Imaging

Abstract: Gramicidin perforated-patch-clamp recordings in brain slices were used to obtain an accurate assessment of the developmental change in the GABAA receptor reversal potential (EGABAA) in embryonic and early postnatal rat neocortical cells including neuroepithelial precursor cells, cortical plate neurons, and postnatal neocortical neurons. Our results demonstrate that there is a progressive negative shift in EGABAA with the most positive values found in the youngest cortical precursor cells. At the early stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
548
2
10

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(602 citation statements)
references
References 54 publications
42
548
2
10
Order By: Relevance
“…Both the time course and the magnitude of the developmental decreases in [Cl βˆ’ ] i reported by Clomeleon are consistent with previous estimates based on electrophysiological measurements (Owens et al, 1996) and the expression profiles of NKCC1 and KCC2 (Rivera et al, 1999;Stein et al, 2004;Yamada et al, 2004;Rivera et al, 2005). Some of these studies showed a rather large variability, both within a given preparation as well as among different cell types, consistent with our finding of a wide distribution of [Cl βˆ’ ] i between individual neurons from young mice ( …”
Section: Clomeleon Reports Neuronal [Cl βˆ’ ] Isupporting
confidence: 92%
See 2 more Smart Citations
“…Both the time course and the magnitude of the developmental decreases in [Cl βˆ’ ] i reported by Clomeleon are consistent with previous estimates based on electrophysiological measurements (Owens et al, 1996) and the expression profiles of NKCC1 and KCC2 (Rivera et al, 1999;Stein et al, 2004;Yamada et al, 2004;Rivera et al, 2005). Some of these studies showed a rather large variability, both within a given preparation as well as among different cell types, consistent with our finding of a wide distribution of [Cl βˆ’ ] i between individual neurons from young mice ( …”
Section: Clomeleon Reports Neuronal [Cl βˆ’ ] Isupporting
confidence: 92%
“…A switch in GABAergic transmission, from depolarization to hyperpolarization, during neuronal development has been demonstrated in many studies (Ben-Ari et al, 1989;Cherubini et al, 1991;Owens et al, 1996) (Fig. 5b, top).…”
Section: Measurement Of Resting [Clmentioning
confidence: 66%
See 1 more Smart Citation
“…To the best of our knowledge, most immature cells that can migrate also accumulate intracellular Cl βˆ’ and are, thus, well equipped to release KCl and to shrink, whereas there is no net force that drives Cl βˆ’ out of the cell in most differentiated neurons. Because of the active accumulation of Cl βˆ’ , immature neurons (Owens et al, 1996) and neuronal stem cells in the ventricular zone (LoTurco et al, 1995) depolarize in response to GABA, whereas differentiated neurons, which no longer move, either hyperpolarize or stabilize their membrane potential (Bormann et al, 1987). Although it is proposed that this depolarizing GABA response might be important physiologically in the context of synapse development (Ben Ari et al, 2004) we suggest that these cells might utilize GABA-gated Cl βˆ’ channels to adjust their cell volume because they are still migrating through the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, under various conditions GABA facilitates neuronal depolarization, including human epileptogenesis (Cohen et al, 2002), after neuronal injury (van den Pol et al, 1996) and during normal early brain development (Ben-Ari et al, 1989;Khazipov et al, 2001;Owens et al, 1996). In the immature brain, activation of GABA A depolarizes the neuron membrane, and within the first and second postnatal weeks of life in mice E Cl Γ€ shifts toward a hyperpolarizing potential thereby leading to inhibitory GABA-mediated responses.…”
Section: Introductionmentioning
confidence: 99%